Differential internalization of hu14.18-IL2 immunocytokine by NK and tumor cell: impact on conjugation, cytotoxicity, and targeting - Reisfeld, RA; Gillies, SD; Rakhmilevich, AL; Yamane, B; Hank, JA; Gubbels, JA; Patankar, MS; Buhtoiarov, TN; Gan, J; Buhtoiarov, IN; Neal, ZC; Sondel, PM (My University, 2011)
The hu14.18-IL2 (EMD 273063) IC, consisting of a GD(2)-specific mAb genetically engineered to two molecules of IL-2, is in clinical trials for treatment of GD(2)-expressing tumors. Anti-tumor activity of IC in vivo and in vitro involves NK cells. We studied the kinetics of retention of IC on the surface of human CD25(+)CD16(-) NK cell lines (NKL and RL12) and GD(2)(+) M21 melanoma after IC binding to the cells via IL-2R and GD(2), respectively. For NK cells, ? 50% of IC was internalized by 3 h and ? 90% by 24 h of cell culture. The decrease of surface IC levels on NK cells correlated with the loss of their ability to bind to tumor cells and mediate antibody-dependent cellular cytotoxicity in vitro. Unlike NK cells, M21 cells retained ? 70% of IC on the surface following 24 h of culture and maintained the ability to become conjugated and lysed by NK cells. When NKL cells were injected into M21-bearing SCID mice, IT delivery of IC augmented NK cell migration into the tumor. These studies demonstrate that once IC binds to the tumor, it is present on the tumor surface for a prolonged time, inducing the recruitment of NK cells to the tumor site, followed by tumor cell killing.
PMID: 21248148